Age Related Change in Thyroid Function - Rahman, Shakila; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2013)
Background: Thyroid hormones play a vital role in metabolism, sensitivity of tissues to other hormones and also in oxygen consumption of almost all cells of the body. However, mild to moderate decrease in function of thyroid gland may occur with advancing age even in apparently healthy elderly subjects. Objectives: To observe age related change in thyroid function status in apparently healthy elderly subjects in Bangladesh. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka between 1st January 2011 and 31st December 2011. Sixty apparently healthy elderly subjects of both sexes aged 50 to 75 years were taken as study group. They were collected from Probin Nibash Hitoishi Shangha, Agargaon, Dhaka. In addition, 30 apparently healthy young adult subjects aged 20-40 years were included as control. For assessment of thyroid function, serum free thyroxine (FT4), free triiodothyronine (FT3) and thyroid stimulating hormone (TSH) levels were estimated by ELISA method. Statistical analysis was done by one way ANOVA, Bonferroni test and Pearsons Correlation Coefficient test as applicable. Results: In this study, mean serum free thyroxine (FT4) and free triiodothyronine (FT3) levels were significantly (p<0.001) lower and serum thyroid stimulating hormone (TSH) level was significantly (p<0.001) higher in apparently healthy elderly subjects in comparison to those of the healthy young subjects. Again, serum FT4 and FT3 levels were negatively correlated whereas serum TSH level was positively correlated with age of the subjects. Conclusion: The present study revealed a progressive decrease in thyroid function with advancement of age. DOI: http://dx.doi.org/10.3329/jbsp.v7i2.14453 J Bangladesh Soc Physiol. 2012, December; 7(2): 72-77